Better Groundwork Can Avoid Troubled Waters: A Developing Country Perspective on Drowning. (14th November 2019) - Samprathi, Madhusudan; Agarwal, Ashish; Jayashree, Muralidharan; Bansal, Arun; Baranwal, Arun; Nallasamy, Karthi; Angurana, Suresh Kumar
Abstract: Objective: Drowning is a leading cause of unintentional injury-related death in low- and middle-income countries (LMICs). This study was undertaken to know the epidemiology, intensive care needs and predictors of outcome of children with drowning. Methods: Records of children below 12 years admitted with drowning to the emergency room and/or paediatric intensive care unit (PICU) of a tertiary care hospital in North India were retrospectively analysed. 'Favourable outcome' was defined as normal neurological status at discharge (normal cognition and no motor deficits) and 'unfavourable outcome' as death or abnormal neurological status at discharge. Multivariable analysis was done for predictors of unfavourable outcome. Results: Twenty-seven children were analyzed, 14 (51.8%) were boys. Median (IQR) age was 18 months (12–30). The median (IQR) duration of submersion was 4 min (3–9). Six children (22.2%) presented in pulseless arrest, and 7 (43.7%) had both hypoxaemia (saturation <94% on room air) and encephalopathy (GCS <13) at admission. Ten children (37%) were transferred to PICU; principal indications being hypoxic ischaemic encephalopathy (HIE) ( n = 6) and ventilation ( n = 4). One child died, four survived with sequalae. Predictors of unfavourable outcome on univariable analysis were hypoxaemia, or pulseless arrest at admission, HIE and need for mechanical ventilation; none of these could predict outcome on multivariable analysis. Conclusion: Hypoxaemia or pulseless arrest at admission, HIE and need for ventilation predict unfavourable outcome. Appropriate on-site resuscitation and early stabilization may improve outcome in children with drowning in LMIC.